En upåagtet dimension i Grundtvigs tanker om “Anskuelsen” - Bugge, K. E. (Grundtvig-Studier, 2006)
En upåagtet dimension i Grundtvigs tanker om “Anskuelsen ” [An unnoted dimension in Grundtvig’s deliberations on “lifephilosophy”] By K. E. Bugge In the introduction to his Northern Mythology (1832) Grundtvig outlines an ideological platform as a basis for rapport and cooperation with his contemporaries. Grundtvig suggests that a broad agreement should be possible on those elements of a life-philosophy, which in theological language are usually termed creation and fall. As far as the ideas of salvation are concerned, however, no unanimity is possible. The following study focuses on the basic assumptions of Grundtvig’s argumentation. How could he be absolutely certain that his readers would readily accept his contention that every one of them, believers and non-believers alike, would agree that the ideas of the divine creation and the fall of man are basic realities of human existence? Such a presumption would certainly not be valid in the secularized cultural context of the following century. In order to answer this question attention is here directed towards the teaching aids used in Danish schools in the subject of Christian Education, especially those, which we know have been used in Grundtvig’s own schooling, and which he later comments upon. The first of these books was published by Grundtvig’s father, Johan Grundtvig under the title Catechismi Forklaring (1779), i.e. a thorough elucidation of Luther’s catechism. Quite a number of such explanatory teaching aids were published during the centuries of Lutheran orthodoxy. Usually they were much too voluminous to be directly used by children. On this background Grundtvig’s uncle, the prominent bishop N. E. Balle in 1791 published a new Lærebog i den evangelisk-christelige Religion, i.e. A textbook of evangelicalchristian religion, a booklet of 104 pages. As this book was officially authorized, it was widely distributed. By 1830 it had been reprinted ten times. In order to make the ideas of God’s creation of the world evident to the children, both these books present the same argument: That just as a house is unable to build itself, in the same manner the world as such must have been built by a creator. Noteworthy is here that the argument in both cases is not rooted in holy scripture but in common sense and everyday experience. Also the argument in support of the idea of the fall of man is notable. Johan Grundtvig in his book combines biblical narrative with common sense. He raises the question, whether the sinfulness of Adam and Eve was inherited by their descendants. His answer is affirmative. Because they were unable to procreate children that were better than themselves, then, of course, their sinfulness was also inherited by their present day descendants. Balle goes directly into an argumentation based on experience and common sense: “Experience makes it clear that men are not as good, as they ought to be. All have some error.” Because of the authorization of the book, Balle’s formulation gained a wide influence during the first half of the century. In the grammar schools preparing the young for university studies the dominating teaching aids in the subject were compendia of two extensive dogmatic expositions published by Ove Hoegh-Guldberg. A compendium by Mathias Galthen (1784, 2nd ed., 1793) was used at the grammar school in Aarhus, which Grundtvig attended during the years 1798-1800. Concerning creation Galthen underscores that the world cannot have created itself, and that “sound reason” convinces us that the world cannot have emerged by coincidence. On the theme of the fall of man he first reiterates the argument forwarded by Johan Grundtvig: That Adam and Eve could not have procreated children that were less sinful than themselves. He then continues: “Experience and Holy Scripture confirms that all men are imperfect”. Notable are here not only the smooth continuation from reason to scripture, but also the order of priority. Everyday experience and “sound reason” provide the intellectual basis necessary for understanding the biblical message. Arguments such as these were inculcated by merciless rote and were, therefore, firmly lodged in the minds of Grundtvig’s readers. On this background he could safely assume that the ideas of creation and fall were readily at hand as preconditions for an understanding of what he had to say. The ideas were imprinted in the minds of his readers as self-evident truths based on experience and common sense and were, therefore, independent of any particular religious conviction. In this way a study of the books used in the Christian Education of his time provide a useful and hitherto unheeded tool for understanding Grundtvig’s argumentation.